EVALUACIÓN DE UN ADITIVO ALIMENTICIO COMERCIAL EN EL DESEMPEÑO PRODUCTIVO DE LA TILAPIA DEL NILO CULTIVADA EN JAULAS FLOTANTES - Virgen Rodríguez, Gerardo (2024)
The production of Nile tilapia (Oreochromis niloticus) has gained great importance in Latin American aquaculture systems, being considered an excellent option for local producers and large companies. However, is commercial growth has generated problems associated with the appearance of diseases that cause an increase in mortality. Due to the above and in order to reduce the use of antibiotics, in recent years producers have begun to use food additives from natural sources. The objective of this study was to evaluate the effect of commercial feed additive on the productive performance of Nile tilapia grown in floating cages. Two treatments were evaluated, commercial food (control) and commercial food + food additive (0.5%), both fed three times a day for a period of 30 days. After the 30 days, the experiment was continued for another 30 days. In total, 450 fish per floating cage were used. Each treatment was carried out by quadruplicate. Biometrics were performed every 15 days, recording wet weight (PH) and total length (LT). The final survival was calculated, and with the PH and LT data obtained, the biomass gained (BG), the daily growth rate (TCD) and the condition factor (FC) were calculated. The results showed that the values of PH, BG, TCD and final survival were significantly higher (P < 0.05) in the treatment that received the feed additive compared to the control treatment from day 30 until the end of the experiment. The growth and survival obtained provide evidence supporting the use of food additives as a strategy by Nile tilapia producers to reduce mortality in commercial culture, without resorting to the use of antibiotics or similar substances.